Effect of balance training on muscle activity and joint moments during perturbed cutting movements - Oliveira, A.; Silva, P. B.; Farina, D.; Kersting, U. G. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Many sports activities involve cutting movements which have been linked to injuries. The ankle and knee joints are particularly at risk when a sudden environmental change perturbes the planned movement. In order to reduce injury incidence, balance training has been used successfully in the past. However, the mechanisms that reduce the risk of injury at the moment of a threat are not completely understood. Therefore the aim of the present study was to verify the effects of balance training on postural reactions to sudden perturbations while cutting. Methods: Twenty-three subjects were randomly assigned to a control group (n=10) and a training group (n=13). The pre- and post-training measurements were based on electromyography (EMG), full-body kinematics and ground reaction force data collected during cutting movements. Subjects were asked to perform 10 cutting movements stepping with the right leg over a moveable force platform. Following these trials, the next trial was set for the force platform to elicit a unexpected rapid movement (10cm at 42cm/s) triggered by foot contact. Integraed EMG (iEMG) from vastus lateralis (VL), biceps femoris (BF), adductor longus (AD) and gluteus maximus (Gmax) as well as knee flexion moment (KFM) were calculated during the absorption period of stance phase (PRP). After pretest the TG subjects performed six weeks of balance training (single standing on a soft mat/wobble board) for the right leg. Differences between groups and training (pre x post) were accessed by t-Student tests at a significance level of p<0.05. Results: sudden perturbations do not alter VL iEMG before and after training for both TG and CG. Before training iEMG was significantly reduced during perturbations for BF (~22%), AD (~17%) and Gmax (~24%) for both TG and CG (p<0.05). After balance training, TG exhibited lower EMG reduction due to perturbations for BF (~6%, p=0.2), no changes for AD (~1%, p=0.34) and increased iEMG for Gmax (~9, p=0.15). In addition balance training induced KFM reduction (~20%, p<0.05) for both normal and perturbed cuttings. The CG showed a similar pattern as in the pretest, with reduced EMG for BF (~16%, p<0.05), AD (~15%, p<0.001) and Gmax (~10, p=0.11), but no changes in KFM in the post-test. Discussion: This is the first study to indicate that balance training improves postural responses during perturbed cuttings. The substantial reductions on iEMG due to perturbations reveal that some presumably protective mechanisms [1] might not occur during a sudden slip, increasing injury risks especially for the knee. Balance training may have increased muscular coordination and facilitated neural drive, keeping muscular stabilization during the perturbation events. At the same time an improved landing strategies that reduce KFM. In conclusion, balance training is effective in improving muscular recruitment for hip and knee muscles, as well as reducing knee moments during sudden perturbations resembling slip episodes during cutting.